The Lived Experiences of Adolescents Living with a Schizophrenic Mother - Indah Mentari Siagian; Suryani Suryani; Titin Sutini (Jurnal Keperawatan Padjadjaran, 2021)
The character building and the development of adolescents are greatly influenced by their mothers. Adolescents who have a schizophrenic mother can undergo problems in their development. This study aimed to explore the lived experiences of adolescents who live with a schizophrenic mother in Bandung. This is a qualitative study with a phenomenological approach. In-depth interviews were conducted with six adolescents aged 17–24 who live with a schizophrenic mother in Bandung. Interview transcripts were analyzed using the Colaizzi method. Eight essential themes emerged in this study. The participants were experiencing various negative emotions while living with their mother and lack of mother-child attachment, but they kept on trying to accept the mother’s condition. They expected that there will be no stigma toward their mother. They needed supports and a friend who could understand and give advice. Notwithstanding the negative situations, they could find a lesson behind the hardship and the father became the source of inspiration. Getting supports from the father and having good friends are the main keys for them to survive. The implications for nursing practice are the need to provide health education programs to help adolescents manage emotions, the development of family-focused care programs, and peer-support groups. Further research is needed in Indonesia to develop appropriate interventions to address mental health problems for adolescents who have schizophrenic mothers in Indonesia.